O uso do léxixo sobre práticas agrícolas na fala dos docentes e discentes de agronomia e de agricultores da região de Dourados/MS - Vasconcelos Rocha, Ioneide Negromonte de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The language of a commonwealth is the most representative form of their culture, since it's through it that every speaker manifest beliefs, traditions, religion and a world view of a society. So, studying the lexicon of a natural language reveals the knowledge of the social history of the commonwealth that uses it. The purpose of this study was to investigate the usage of the lexical variation current on agricultural practices of urban speakers of Higher Education institutions (IES) and among speakers of rural area in the great region of Dourados on Mato Grosso do Sul state, which are distributed in the following groups: A - teachers from the graduation course in Agronomy, B - students from the graduation curse in Agronomy, C - farmers. This research is based on theoretical assumptions of Lexicology, adding some fundamentals of Dialectology and Sociolinguistics, two areas of linguistics which have the language in use as object of study, with the focus turned to the variation phenomenon. Regarding the Lexicology, specifically the lexical-semantic aspects, studies were oriented by Sapir (1961), Rey (1970) Pottier (1978), Pottier (1978), Lyons (1979), Biderman (2001); the base of the Dialectology has as its source Ferreira e Cardoso (1994), Ferreira et al (1996); of the Sociolinguistics, Tarallo (1986), Preti (2003) Bortoni-Ricardo (2004), among others. Corpus Linguistics, according to precepts of Berber Sardinha (2003, 2004, 2005) contributed to the realization of the methodological procedures. The lexicon is analyzed in a process of interaction with its own social environment, enabling the identification of the differences and similarities in levels of use, which can be observed both in technical lexical units (inherent of Literature farming practices) and in everyday speech, revealing the lexical variation in the speech of informants. Thus, in the analysis, the Lexical and Semantic Fields (CLS) were essential for the description of ...

A língua de um povo é a forma mais representativa de sua cultura, visto que é por meio dela que cada falante manifesta as crenças, os costumes, os valores, a religião, a visão de mundo de uma sociedade. Assim, estudar o léxico de uma língua natural revela o conhecimento da história social do povo que a utiliza. O propósito deste estudo foi investigar a variação do léxico corrente sobre práticas agrícolas em uso, no caso de falantes urbanos de Instituições de Ensino Superior (IES) e em falantes do meio rural da Região da Grande Dourados no Estado de Mato Grosso do Sul, que se distribuem nos seguintes grupos: A - docentes do curso de graduação em Agronomia, B - estudantes em formação no curso de graduação em Agronomia e C - agricultores. Esta pesquisa baseia-se nos pressupostos teóricos da Lexicologia, acrescentando fundamentos da Dialetologia e da Sociolinguística, duas áreas da linguística que têm a língua em uso como objeto de estudo, com o enfoque voltado para o fenômeno da variação. No que concerne a Lexicologia, especificamente os aspectos léxico-semânticos, os estudos foram orientados por Sapir (1961), Rey (1970), Pottier (1978), Lyons (1979), Biderman (2001); a base da Dialetologia tem como fonte Ferreira e Cardoso (1994), Ferreira et al (1996); da Sociolinguística, Tarallo (1986), Preti (2003), Bortoni-Ricardo (2004), dentre outros. A Linguística de Corpus, segundo preceitos de Berber Sardinha (2003, 2004, 2005), contribuiu para a realização dos procedimentos metodológicos. O léxico é analisado dentro de um processo de interação com o próprio meio social, possibilitando a identificação das diferenças e semelhanças dos níveis de uso, que podem ser observados tanto em unidades lexicais técnicas (próprias da Literatura de práticas agrícolas) quanto na fala corrente, revelando a variação lexical na fala dos informantes. Assim, na análise foram essenciais os Campos...
Keywords: Applied linguistics; Linguistica aplicada; Língua portuguesa - Lexicologia; Sociolinguística; Língua portuguesa - Variação; Linguística de corpus; Linguagem e cultura - Dourados (MS); Agronomia – Terminologia